Undergraduate radiology teaching in a UK medical school: a systematic evaluation of current practice. Issue 5 (May 2016) - Jacob, J.; Paul, L.; Hedges, W.; Hutchison, P.; Cameron, E.; Matthews, D.; Whiten, S.; Driscoll, P.
Abstract : Aim: To use the Royal College of Radiologists' Undergraduate Radiology Curriculum (RCR URC) as an innovative tool to review undergraduate radiology teaching and ensure it is comprehensive and balanced. Materials and methods: Quantitative and qualitative methods were used to audit and review radiology teaching for students in years 1–3. All radiological teaching on the course was mapped against the RCR URC learning outcomes. An online survey of students in year 3 ( n =138) was conducted using Likert (1–5), multiple choice, and free-text questions. Results: There were 954 instances of radiology teaching, with 70% occurring during lectures. Radiology teaching was mapped to 81 of the 96 RCR URC learning outcomes (84.4%). Forty-seven of 138 students responded to the survey. They expressed confidence in understanding what basic imaging entails ( x ¯ =4.23) and the risks associated with various imaging techniques ( x ¯ =4.34). They were also confident in chest radiograph interpretation ( x ¯ =3.62), but were less confident understanding abdominal radiographs ( x ¯ =2.87). In free-text comments, students requested more tutorial-type teaching and ultrasound instruction. Conclusion: The RCR URC is an effective tool for auditing undergraduate radiology teaching, and other medical schools may, therefore, benefit from using this method. This evaluation process incorporating audit and feedback has identified areas for curriculum development. These include incorporating ultrasound into teaching sessions, delivering more small-group teaching, and introducing clinical placements in radiology departments. Highlights: The RCR URC can be used to audit undergraduate radiology teaching in medical schools. Teaching was overall comprehensive with some minor areas for improvement. Increasing small group tutorials and incorporating ultrasound into the curriculum would address these deficiencies.